Language learners’ emotion regulation and enjoyment in an online collaborative writing program - Zhang, Zhipeng; Gao, Xuesong (Andy); Liu, Ting; Lee, Chwee Beng (Studies in Second Language Learning and Teaching, 2022)
Collaborative learning in online contexts is emotionally challenging for language learners. To achieve successful learning outcomes, language learners need to regulate their emotions and sustain positive emotions during the collaborative learning process. This study investigated language learners’ emotion regulation and enjoyment, the most extensively researched positive emotion in foreign language learning, in an online collaborative English learning environment. In the study, we collected data by surveying 336 Chinese students majoring in English who collaboratively completed a series of English language writing tasks in 108 online groups facilitated by a social media app (WeChat). Principal component analysis revealed two primary types of emotion regulation: peer regulation and group regulation. The analysis also revealed one factor underpinning enjoyment: enjoyment of online collaboration. Correlation analysis showed medium and positive relationships between peer regulation, group regulation, and enjoyment of online collaboration. Structural equation modeling analysis further found that group regulation exerted a medium-sized direct effect on enjoyment of online collaboration. Peer regulation affected enjoyment of online collaboration moderately and indirectly via group regulation. The theoretical and pedagogical implications of the findings can help to optimize face-to-face and online collaborative language learning activities.